LINGKUNGAN KERJA DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN PADA PT JASAMARGA RELATED BUSINESS JAKARTA - Eigis Yani Pramularso; Septiani Latifah (Jurnal Ekonomi STIEP, 2023)
Increased competition makes companies have to be more prepared and try to excel from other companies. One of the things that makes a company superior is its employees who are competent, responsible, and strive to continuously improve their performance to achieve the vision and mission. One that supports improving employee performance is a safe, comfortable and adequate work environment. The purpose of this study was to determine the effect of the work environment on employee performance at PT Jasamarga Related Business Jakarta. The data collection method used was a questionnaire or questionnaire method with a sample of 65 employees in the operational section, HR department and project department. The data analysis technique used is the correlation coefficient test, determination, and simple regression. The results of correlation calculations show a moderate relationship between the work environment and employee performance. The results of the study also show that there is a significant and positive influence between the work environment and employee performance at PT Jasamarga Related Business Jakarta.